Pengembangan Aplikasi Rekomendasi Musik berdasarkan Detak Jantung pada Platform Android - Muhammad Salman Ramadhan; Ratih Kartika Dewi; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Music is one of the important aspects of life but there is always a problem regarding choosing the right music for the right occasion. With today's technology growth, there are already so many music players that provide a different kind of music genre so that people can pick the one that fits their taste. Music players also provide recommendations for which music is up to your palette taste but the recommendation is not always right to the occasion we are facing or enjoying right now. The Music Recommendation System based on Heartrate help user to find their music that fits with the context they are in. The development oh this system is to make an android application and using the expert system method with forward chaining. this system will process input that the user input and the output will be a recommendation of music that fits the expert rule. Functional testing of this system resulting in a valid outcome which means this system grade is 100%. Usability testing of this system outcome is 76.5 in value of system usability scale which means it's acceptable. This application can be used to find music that fits a context with the help of heart rate.